Dissolution of heat activated serpentine for CO2 sequestration: The effect of silica precipitation at different temperature and pH values. (March 2019) - Farhang, F.; Oliver, T.K.; Rayson, M.S.; Brent, G.F.; Molloy, T.S.; Stockenhuber, M.; Kennedy, E.M.
Highlights: The dissolution kinetics of roasted lizardite at different T and pH were studied. An initial rapid liberation of Mg 2+ followed by a very slow extraction was observed. Increasing temperature caused an increase in the rate of Mg extraction initially. The extent of extraction of Mg 2+ decreased due to precipitation of silica. Silica re-precipitation at high temperature and S/L was demonstrated. Abstract: The dissolution of magnesium silicate minerals such as serpentine in aqueous solutions saturated or near saturated with carbon dioxide (CO2 ) enables its subsequent reaction to form magnesium carbonate, a process called aqueous mineral carbonation. The dissolution rate of magnesium ions (Mg 2+ ) from thermally activated serpentine and the factors influencing the rate and extent of dissolution have been studied in our research group. The current contribution focuses on the effect of temperature and pH on the dissolution of heat activated lizardite (a polymorph of serpentine). The extent of dissolution of thermally activated lizardite was measured experimentally as a function of temperature (25 °C ≤ T ≤ 75 °C) and pH (1.2 ≤ pH ≤ 9.8). It was found that at higher temperatures the level of Mg extraction is greater during the initial stage of dissolution but is then hindered by the re-precipitation of amorphous silica. Thermodynamic modelling was used to assess the susceptibility of solid phase formation and confirmed the likelihood of re-precipitation of amorphous silica from the solutions. For the first time, in this work, the crackling core model (CCM) was used to model experimental data at different pH values.